Case Report: PAFAH1B1 Mutation and Posterior Band Heterotopia With Focal Temporal Lobe Epilepsy Treated by Responsive Neurostimulation - Gilliam, Frank G.; Ssentongo, Paddy; Sather, Michael; Kawasawa, Yuka I. (Frontiers in Neurology, 2021)
Subcortical band heterotopia (SBH), also known as double cortex syndrome, is a malformation of cortical development that may be caused by inherited or somatic gene variants. We present a case of a young adult with posterior SBH and common phenotypical features of pharmacoresistant focal neocortical temporal lobe epilepsy and moderately severe static encephalopathy. Genomic blood analysis identified a pathogenic somatic mosaicism duplication variant of the PAFAH1B1 gene. Despite bilateral cortical MRI abnormalities, the interictal and ictal EEG findings indicated a focal epileptogenic region in the left posterior temporal region. Chronic responsive cortical neurostimulation across two four-contact depth electrodes placed 5 mm on either side of the maximal interictal spiking identified during intraoperative electrocorticography resulted a consistent 28% reduction in duration and propagation of electrographic seizures. Although electrographic seizures continued, the family reported no clinical seizures and marked improvement in behavior. This observation supports that focal neuromodulation can control clinical seizures of consistently localized neocortical origin despite genetic etiology, bilateral structural brain abnormalities, and continuation of milder electrographic seizures.